2010
DOI: 10.1542/peds.2009-1635
|View full text |Cite
|
Sign up to set email alerts
|

Team Training in the Neonatal Resuscitation Program for Interns: Teamwork and Quality of Resuscitations

Abstract: Trained participants exhibited more frequent teamwork behaviors (especially the HFT group) and better workload management and completed the resuscitation more quickly than did control subjects. The impact on team behaviors persisted for at least 6 months. Incorporating team training into the NRP curriculum is a feasible and effective way to teach interns teamwork skills. It also improves simulated resuscitation quality by shortening the duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 12 publications
2
151
0
Order By: Relevance
“…47,[109][110][111][112][113][114][115][116][117][118][119] A meta-analysis of 8 randomized controlled trials assessing knowledge at course conclusion demonstrated no significant benefit of training with high-fidelity manikins compared with low-fidelity manikins. 47,110,111,[116][117][118]120,121 This is supported by 1 additional nonrandomized trial demonstrating no substantial benefit of high-fidelity training on knowledge acquisition.…”
Section: Manikin Fidelity Eit 623 -Updatedmentioning
confidence: 99%
“…47,[109][110][111][112][113][114][115][116][117][118][119] A meta-analysis of 8 randomized controlled trials assessing knowledge at course conclusion demonstrated no significant benefit of training with high-fidelity manikins compared with low-fidelity manikins. 47,110,111,[116][117][118]120,121 This is supported by 1 additional nonrandomized trial demonstrating no substantial benefit of high-fidelity training on knowledge acquisition.…”
Section: Manikin Fidelity Eit 623 -Updatedmentioning
confidence: 99%
“…When inductively searching for conceptual themes shared across studies, we identified 7 studies comparing high with low physical realism simulation as part of the educational intervention, and conducted a metaanalysis pooling the results of these studies. [26][27][28][29][30][31][32] We narratively discuss the other studies with nonrecurrent themes. [33][34][35][36][37][38][39][40][41][42][43] …”
Section: Synthesis: Comparison Of Simulation Versus Other Types Of Tesmentioning
confidence: 99%
“…Seven studies [26][27][28][29][30][31][32] compared the use of high versus low physical realism simulators for TES as an educational modality (Fig 4). Meta-analysis of these studies revealed pooled effects of small magnitude favoring high physical realism for nontime skills (4 studies; ES = 0.49; P , .001) and learner reactions (3 studies; ES = 0.70; P , .01).…”
Section: Comparison Of High Versus Low Physical Realism Simulationmentioning
confidence: 99%
“…In fact, several studies have reported that the improvement in individual technical skills is no longer significant at 6 months after an intervention. 28 Our study evaluated the efficiency of resuscitation performed on a manikin; however, the impact in real-life neonatal resuscitation remains unknown. In other words, the study reached the third level of Kirkpatrick' s model to evaluate training programs.…”
Section: Figurementioning
confidence: 99%